Capacidade adaptativa às mudanças climáticas de agricultores familiares no semiárido brasileiro - César Nunes de Castro (Instituto de Pesquisa Econômica Aplicada (IPEA), 2024)
– As a result of several combined factors (climate, water availability, technology, etc.), production and income generated by family farmers in the Brazilian semi-arid region are relatively low. The climate changes projected for the Brazilian semi-arid region, if confirmed, will impact regional agricultural activity. The objective of this paper is, in the context of family farming, to carry out an assessment of the potential impacts of climate change in the semi-arid region of Brazil, as well as the adaptive capacity of these farmers to the phenomenon and alternatives to mitigate possible impacts through specific public policies.
Keywords: Q1; Q18; 330; family farming; semiarid region; climate change